2011
DOI: 10.3928/19404921-20101207-01
|View full text |Cite
|
Sign up to set email alerts
|

Older African American Women's Beliefs, Attitudes, and Behaviors About Breast Cancer

Abstract: Breast cancer poses a greater risk for African American than Caucasian women due to persistent health disparities. To reduce mortality risk, culturally specific knowledge is needed to support and encourage regular breast cancer screening and risk-reduction behaviors in older African American women. The specific aims of this study were to identify social, cultural, and behavioral factors associated with regular participation in breast cancer screening and risk-reduction behaviors; examine health beliefs that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…Participants demonstrated internal and external resources for strength and highlighted those resources as important sources of physical and spiritual support during diagnosis and treatment, when family members and a variety of other individuals provided support and assistance with the management of daily living. Similar to the current findings, African American survivors in previous studies reported giving back in the form of providing support to family, friends, and other cancer survivors as an important coping strategy and source of social support (Hamilton et al, 2009; Swinney & Dobal, 2011). However, previous research with the survivors also revealed some perceived stigma and a lack of support related to cancer, leading to additional isolation during treatment (Hamilton, Powe, Pollard, Lee, & Felton, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Participants demonstrated internal and external resources for strength and highlighted those resources as important sources of physical and spiritual support during diagnosis and treatment, when family members and a variety of other individuals provided support and assistance with the management of daily living. Similar to the current findings, African American survivors in previous studies reported giving back in the form of providing support to family, friends, and other cancer survivors as an important coping strategy and source of social support (Hamilton et al, 2009; Swinney & Dobal, 2011). However, previous research with the survivors also revealed some perceived stigma and a lack of support related to cancer, leading to additional isolation during treatment (Hamilton, Powe, Pollard, Lee, & Felton, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Spirituality has been shown to be associated with well-being during cancer treatment (Visser, Garssen, & Vingerhoets, 2010). Multiple qualitative studies of African American cancer survivors have suggested a link between the spiritual and religious practices of the survivors and perceptions of social support from God and their faith communities (Hamilton et al, 2007, 2009; Swinney & Dobal, 2011; Thompson, Littles, Jacob, & Coker, 2006). Interventionists have demonstrated the value of incorporating spirituality into cancer support programs for African Americans in rural areas (Hamilton et al, 2007, 2009; Martin et al, 2011; Powell et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our measure of stigma captures primarily the notion that cancer is perceived as a death sentence and this attitude results in members of their social networks responding with pity, inappropriate comments, or the complete withdrawing of support. In spite of the educational programs and advances in cancer care, it appears that the perspective of cancer being equated with death persists within the African American community (Swinney & Dobal, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Our findings confirm results from previous studies that have identified fatalistic attitudes towards cancer outcomes among African American women and the attitude that cancer is a death sentence. [8][9][10][11] For example, Hall and colleagues (2008) conducted a study with an ethnically diverse sample of women and found that women who believed that breast cancer could not be cured if found early were more likely to be African American. 9 Programs designed to promote early detection of cancer among underserved African American women must seek to overcome these negative attitudes toward early detection of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Women who perceive a cancer diagnosis as a ''death sentence'' typically do not believe that screening and early detection will improve survival after a cancer diagnosis. 10,11 A woman's belief in the benefit of screening may be influenced by her social network, her health care providers, and the media. 12,13 Women who have a regular health care provider and who undergo routine checkups may discuss the benefit of early detection with their providers, who usually recommend screening.…”
Section: Introductionmentioning
confidence: 99%